STRATEGIC MANAGEMENT OF RURAL ROAD MAINTENANCE IN NORTH BARITO REGENCY - Subiyantoro Subiyantoro (Jurnal Teknologi Berkelanjutan, 2014)
Road maintenance management in the rural area by the government of North Barito Regency has not gone well. Many rural roads are not maintained because of a limited budget and the government agencies and the private sector on the maintenance of rural roads are not well coordinated, therefore the need for structured management strategies is in demand. This study aims to create a plan of management strategies, and determine the priority of rural road maintenance in North Barito Regency. The analysis of the research was carried out by the analysis of rural road infrastructure using the analysis of assessment criteria and SWOT analysis, analysis of management sequence of the rural road using the Most Desirable analysis by society (MDm), and analysis of the rural roads maintenance costs. The results of the inventory data shows that there are 154 rural roads recorded in the village. Based on the analysis of the assessment criteria, there are 130 roads and the SWOT analysis shows 115 roads, therefore, the rural roads that are categorized in the analysis of rural road infrastructure to be maintained are 115 rural roads. The sequence analysis management using MDm analysis is used to determine the priority order of 115 village road maintenance road. The cost analysis determination is based on government funding sources Barito Utara as much as Rp 1.110.000.000, while the budget plan that is allocated for the maintenance for the 115 village roads is Rp 3.532.482.275, it is therefore necessary to create a strategy. The preparation of the strategy is divided into a long-term strategic plan for five years, and short-term strategic plans for one year. In the first year, there are 36 packages with the allocation of Rp 1.110.000.000, for the second year there are 35 packages with funds allocated as much as Rp 1.137.200.000, for the third year there are 39 packages with funds allocated Rp 1.165.650.000, while there is one work package of 5 packages with funds allocated Rp.168.199.850. All packages of rural road maintenance work can be done with the assumption that each year has been allocated to the budget plan and the planned work program can be completed in 4 years. It is suggested to make some sort of mapping of the location of the inventory, assessment criteria approach in more detailed and accurate to get the actual results.